Analaysis of Cholinesterase and SGPT Levels in Blood in Farmers Using Pestisida - Setyawan, I Gede Yudia; Purwati, Purwati; Harningsih, Tri (Indonesian Journal of Global Health Research, 2024)
Pesticides can enter the body through inhalation, so to find out poisoning or exposure to pesticides in the body, it is necessary to check Cholinesterase levels. The accumulation of pesticides in the liver triggers an increase in the number of free radicals and results in damage to hepatocyte cells and increases SGPT levels. The purpose of this study was to the levels of cholinesterase and SGPT in farmers who use pesticides. The research metodes, This type of analytic observational research with a cross-sectional study design. Total sample of 20 people selected by quota sampling. The results showed that the cholinesterase levels of the respondents were obtained between 6985 U/L to 12489 U/ and the SGPT levels of 19 respondents were 4 U/L – 42 U/L and 1 respondent had SGPT levels of 52 U/L. The cholinesterase levels of 20 respondents were within normal limits, namely less than 12920 U/L, while the SGPT levels of 19 respondents were within normal limits of less than 59 U/L and 1 respondent exceeded the normal limits of more than 50 U/L.